Farnesyl pyrophosphate is an endogenous antagonist to ADP-stimulated P2Y12 receptor-mediated platelet aggregation - Högberg, Carl; Gidlöf, Olof; Deflorian, Francesca; Jacobson, Kenneth A.; Abdelrahman, Aliaa; Müller, Christa E.; Olde, Björn; Erlinge, David (Thrombosis and Haemostasis, 2012)
Farnesyl pyrophosphate (FPP) is an intermediate in cholesterol biosynthesis, and it has also been reported to activate platelet LPA (lysophos-phatidic acid) receptors. The aim of this study was to investigate the role of extracellular FPP in platelet aggregation. Human platelets were studied with light transmission aggregometry, flow cytometry and [35S]GTPγS binding assays. As shown previously, FPP could potentiate LPA-stimulated shape change. Surprisingly, FPP also acted as a selective insurmountable antagonist to ADP-induced platelet aggregation. FPP inhibited ADP-induced expression of P-selectin and the activated glycoprotein (Gp)IIb/IIIa receptor. FPP blocked ADP-induced inhibition of cAMP accumulation and [35S]GTPγS binding in platelets. In Chinese hamster ovary cells expressing the P2Y12 receptor, FPP caused a right-ward shift of the [35S]GTPγS binding curve. In Sf9 insect cells expressing the human P2Y12 receptor, FPP showed a concentration-dependent, although incomplete inhibition of [3H]PSB-0413 binding. Docking of FPP in a P2Y12 receptor model revealed molecular similarities with ADP and a good fit into the binding pocket for ADP. In conclusion, FPP is an insurmountable antagonist of ADP-induced platelet aggregation mediated by the P2Y12 receptor. It could be an endogenous antithrombotic factor modulating the strong platelet aggregatory effects of ADP in a manner similar to the use of clopidogrel, prasugrel or ticagrelor in the treatment of ischaemic heart disease.
Keywords: ADP receptors; platelet pharmacology; platelet physiology